2018
DOI: 10.1111/imm.13019
|View full text |Cite
|
Sign up to set email alerts
|

Basics of memory B‐cell responses: lessons from and for the real world

Abstract: Summary The production of pathogen‐specific B cells and antibodies underlies protective immunity elicited by most vaccines and many infections. Humoral immunity follows a regulated process by which high‐affinity antibody‐secreting plasma cells and memory B cells are generated. Yet for certain pathogens, protective immunity is inefficiently generated and/or maintained. For example, Dengue virus infections lead to lasting immunity against re‐infection by the same serotype. However, if infected with a different D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 108 publications
1
18
0
Order By: Relevance
“…Splenectomy has important consequences for the homeostasis of the immune system, and in particular, the B cell compartment seems to be the most involved. Our study confirmed the many observations regarding the impairment of B lymphocytes in these patients [16], showing that splenectomized patients (group B) have increased levels of B-naive and reduced levels of classswitched and unswitched memory B cells. In contrast, the autotransplanted patients did not present any significant differences for all of the evaluated B lymphocyte subsets compared to normal subjects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Splenectomy has important consequences for the homeostasis of the immune system, and in particular, the B cell compartment seems to be the most involved. Our study confirmed the many observations regarding the impairment of B lymphocytes in these patients [16], showing that splenectomized patients (group B) have increased levels of B-naive and reduced levels of classswitched and unswitched memory B cells. In contrast, the autotransplanted patients did not present any significant differences for all of the evaluated B lymphocyte subsets compared to normal subjects.…”
Section: Discussionsupporting
confidence: 90%
“…The spleen is considered the site at which newly formed B lymphocytes are induced to mature into IgD recirculating B cells, the population that is able to initiate the humoral immune responses. In normal subjects, the B-naive cells rapidly recognize the antigen, proliferate and differentiate into short-lived plasma cells or germinal center B cells [16], thus contributing to T cell-dependent immune responses and leading to germinal center formation in follicles of secondary lymphoid organs. B cell interactions with follicular helper T cells represent a crucial step in the production of their memory B cell counterparts or plasma cells that produce high affinity, somatically mutated, class-switched antibodies [17].…”
Section: Discussionmentioning
confidence: 99%
“…Administering a recall Ag injection some time after vaccination generates responders Ab-secreting cells (Ab-SCs). These cells comprise both MCs, that can be stimulated to differentiate and produce Abs upon new Ag encounter ( McHeyzer-Williams et al, 2015 ; Dogan et al, 2009 ; Mesin et al, 2016 ; Inoue et al, 2018 ), and residual PCs formed during previous maturations; PCs belonging to the long-lived pool are capable of surviving up to a human lifetime in the absence of division ( Wong and Bhattacharya, 2019 ; Crotty et al, 2003 ). The affinity distribution of Ab-SCs is assumed to be a weighted mixture of the MC and PC populations, with fractions equal respectively to and , where the value of is expected to depend on the conditions under which the system is probed.…”
Section: Resultsmentioning
confidence: 99%
“…LLPCs are the sources of this durable Ab production (41)(42)(43)(44)(45)(46). Humoral immunity to chronic infections such as those caused by HIV and human papillomavirus, where viral Ags can persist in the host, are more complex (47). Given the acute nature of SARS-CoV-2 infections, chronic infections will not be discussed further in this article.…”
Section: Fundamentals Of B Cell Responses To Acute Viral Infectionsmentioning
confidence: 99%